An Arts-Based Exploration of Classroom Management Through Portraiture (LEARNing Landscapes, 2022)
This arts-based research uses portraiture and appreciative inquiry to explore Bachelor of Education teacher candidates’ conceptions of classroom management. A total of 270 sets of observational notes completed by 90 teacher candidates during their school practicum placements were used to inform the researchers’ creation of arts-based literary and painted learner portraits. The research addresses the questions: (1) What characteristics do teacher candidates associate with different types of learners?; (2) How might teacher-educators critically unpack these assumptive characteristics to better prepare teacher candidates for working in diverse classrooms?; and (3) How might an arts-based way of knowing enhance teacher candidates’ understandings of classroom management?
Keywords: arts-based research; appreciative inquiry; portraiture; teacher education; classroom management